Clinicoepidemiological profile and outcome of pyogenic liver abscess in children up to 12 years age (Indian Journal of Child Health, 2020)
Background: Pyogenic liver abscess (PLA) is common in the Indian pediatric population and is an under-researched topic. It is a significant cause of morbidity and mortality. Objective: The objective of this study was to review the clinicoepidemiological profile of PLA in children and to evaluate the outcome in terms of mortality, prolonged hospital stay (>3 weeks), and complications during a 1-month follow-up period. Materials and Methods: This was a hospital-based prospective observational cohort study conducted in the pediatric department of a tertiary care hospital. A total of 59 children of either sex up to 12 years of age were enrolled in the study. Associations of outcomes and various clinical symptoms were assessed using Student’s t-test and Chi-square test. Results: The median age was 7 years (ranging from 3 to 12 years) with a male preponderance (64.41%). Fever (94.91%) was the most common presenting symptom. A majority (61%) of the abscesses were found in the right lobe. Ultrasonography (USG) was the mainstay of diagnosis. About 54.23% of children were managed only medically, while 23.73% and 22.03% of children underwent USG-guided pigtail insertion and percutaneous aspiration, respectively, in addition to intravenous antibiotics. Pus and blood culture obtained from the abscess site that was sterile in more than 50% of cases. The mean duration of hospital stay was 15.34±4.71 days. There were 3 (5.08%) mortalities. The type of intervention done was shown to have a significant association with the length of hospital stay, mortality, complications, and findings on follow-up USG. Conclusions: The PLA is an important cause of morbidity in children below 12 years of age. If not managed appropriately, it may lead to rupture and mortality.